Specific Features and Stages of Evolution of the Spanish Genre Painting in the 17th Century - Sonina, Irina M. (Actual Problems of Theory and History of Art, 2013)
The article is devoted to the study of important and poorly understood topic related to the identification and analysis of the specifics and the evolution of the genre in the Spanish 17th c. painting. The relevance of the research is due, on the one hand, the need for a comprehensive study of the Spanish art, on the other hand, the need of the study of the genre, analyzed in the context of theory and history of fine arts. Analysis of the creative works of Spanish artists of the 17th c. allowed to create an overall picture of the development of the genre trends in their art and to analyze the features of the genre painting.
Keywords: genre painting; the Spanish painting of the 17th c; evolution; specific features